Implementing Independent Learning Curricula: A Case Study from MAN 2 Kediri, Indonesia - Nur Kholifah Akrom; Abd. Aziz; Agus Zaenul Fitri; Venant Hakizimana (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2023)
This research examines four aspects of the independent learning curriculum at MAN 2 Kediri City, namely objectives, materials, methods and evaluation. The main focus is to examine the impact on the development of students' independence and their readiness to face future challenges. This qualitative case study involves field observations, interviews with educational figures, and document analysis within an ethnographic framework. The research results show that the curriculum is designed to shape student character according to the national education profile, with broad and inclusive content. This approach focuses on developing critical thinking and problem solving abilities through a variety of teaching methods. The evaluation uses a multilevel assessment strategy to ensure the effectiveness of the curriculum. The implementation was successful, marked by student academic achievement. However, there are limitations to this research, namely the absence of visual data analysis. For this reason, further studies are needed. These findings contribute to curriculum theory, by proposing a framework that prepares students with essential skills and attitudes for the 21st century.